Spiky pygmy devils: revision of the genus Discotettix (Orthoptera: Tetrigidae) and synonymy of Discotettiginae with Scelimeninae - Skejo, Josip; Pushkar, Taras I.; Kasalo, Niko; Pavlović, Marko; Deranja, Maks; Adžić, Karmela; Tan, Ming Kai; Rebrina, Fran; Muhammad, Amira Aqilah; Abdullah, Nurul Ashikin; Japir, Razy; Chung, Arthur Y. C.; et al. (Zootaxa, 2022)
Spiky pygmy devils (Tetrigidae: Discotettiginae) are, because of the spiky pronotal projections and widened subapical antennal segments, among the most unique pygmy grasshoppers in Southeast (SE) Asia. The taxonomy of the group was unclear in the past, so this study brings a taxonomic and biographical review of the genus Discotettix Costa, 1864. New terminology of the pronotal projections is proposed for Scelimeninae. All valid species hitherto included in the genus are redescribed; a new genus is established for Discotettix shelfordi Hancock, 1907, Disconius Skejo, Pushkar et Tumbrinck gen. n., so a new combination is established for the species (Disconius shelfordi comb. n.). New synonymy is established: Discotettix selysi Bolívar, 1887 = Discotettix selangori Mahmood, Idris et Salmah, 2007 syn. n. Three new species are described and a key to Discotettix species is provided. The genus now includes seven species (1) Discotettix aruanus Skejo, Pushkar et Tumbrinck sp. n. from Aru; (2) D. belzebuth (Serville, 1838) from Borneo; (3) D. doriae Bolívar, 1898 stat. resurr. from the Mentawai islands; (4) D. kirscheyi Skejo, Pushkar, Tumbrinck et Tan sp. n. from Northeast (NE) Borneo; (5) D. scabridus (Stål, 1877) endemic to Mindanao and Samar; (6) D. selysi Bolívar, 1887 from Sumatra and peninsular Malaysia; (7) D. sumatrensis Skejo, Pushkar et Tumbrinck sp. n. endemic to southern Sumatra. Moreover, Discotettix is again subdivided into two subgenera: Mnesarchus Stål, 1877 stat. resurr. (D. scabridus) and nominotypical one (other species). Widened antennal segments are the only character common to all Discotettiginae genera, but this trait does not have great taxonomic importance, as it is homoplastic, meaning that it appeared in distant Tetrigidae groups independently. Discotettix is herewith transferred to the subfamily Scelimeninae and accordingly, the subfamily Discotettiginae Hancock, 1907 syn. n. becomes a junior synonym of the subfamily Scelimeninae Bolívar, 1887. The tribe Discotettigini stat. resurr., on the other hand, gathers corticolous genera of the Scelimeninae (Austrohancockia Günther, 1938, Bidentatettix Zheng, 1992, Disconius gen. n. Discotettix, Eufalconius Günther, 1938, Gibbotettix Zheng, 1992, Paragavialidium Zheng, 1994, Gavialidium Saussure, 1862, and Tegotettix Hancock, 1913), while the tribe Scelimenini becomes restricted to amphibious taxa. All taxa are described and amply depicted with both museum specimens and in situ photographs. An identification key is provided. The morphology and function of widened antennae in Discotettigini are discussed.